Amerikan Psyko - Gandillac, de Çiva (France, 2010)
Shot before the election of Barack Obama and filmed with a small pen camera during an improvised trip, this documentary gives voice to Americans who are afraid, who doubt, who advocate a strong America, in short, to a conservative America.
Verzio Film Festival Submission
Keywords: Documentary films